THE EFFECTIVENESS OF ISO 9001:2008 AT POLITEKNIK KESEHATAN MANADO - Cindy, Tuju Angel; Saerang, David P.E; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract :Products and services are the result of activities or processes that transform inputs into outputs and the quality of products and services is directly related to the quality of the process that produces them. The purpose of this study is to analyze how Politeknik Kesehatan Kemenkes Manado implements ISO 9001:2008 standard in order to meet the academic, professional and society’s expectations. ISO is an international standard that gives requirements for an organization related to its quality management system which focuses on meeting customer expectation and delivering customer satisfaction. In order to get the data needed for this study, the study uses data collection tools such as observation, interview and literature analysis. From primary and secondary data. The results of this study show that the implementation of ISO 9001:2008 in Politeknik Kesehatan Kemenkes Manado is successful and meets the standards of ISO 9001:2008, Some supporting facilities and infrastructures as well as the educational service and process are qualified according to the standard. Keywords : ISO 9001:2008, Customer expectation